Social impact of renewable energy systems: solar energy system in vulnerable community case study - Yeison Alberto Garcés- Gómez; Vladimir Henao- Céspedes; Diana Marcela Gómez Sánchez; Ángel Andrés López Trujillo; Nicolás Toro García (Bulletin of Electrical Engineering and Informatics, 2021)
Photovoltaic lighting systems are unable to reach people with low purchasing power due to high installation costs, so they have traditionally been concentrated in families with high purchasing power and currently do not take into account the social power that this type of system represents. This article analyzes through bibliometric review the effect that lighting can have on human development and how a good lighting system can positively affect a community environment. It is proposed the social design of a photovoltaic lighting system which will be installed in a vulnerable community with resources obtained by the community itself and the whole process of accompaniment achieving a satisfactory impact on the community and achieving integration between the same from community participation. The development of workshops with the children of the community has also been proposed, leading to the training and recognition of alternative energy systems as a strategy of social appropriation.